EVALUATION OF PHULE TRIVENI SIRE FOR ESTIMATED BREEDING VALUE OF LIFETIME TRAITS* (Indian Journal of Animal Production and Management, 2015)
The data of Phule Triveni crossbred cows of FJG, H, 3H, 4H, 5H and 6H generations maintained at Research Cum Development Project on Cattle, MPKV, Rahuri for a period of 33 years (1977 to 2009) were used to estimate sire’s breeding value for lifetime performance traits. Lifetime traits were herd life, productive life, lifetime milk yield, number of days in milk, lifetime milk yield per day of productive life and lifetime milk yield per day of lactating life. The least-squares method was used to obtain the estimates of breeding values. The estimated breeding values (EBVs) of sires showed large genetic variation between sires for lifetime traits. The estimated breeding values (EBVs) for sires ranged from 893.92 to 1065.63 days for age at first calving, 4237.73 to 12785.71 kg for lifetime milk yield, 667.98 to 1389.52 days for number of days in milk, 1929.18 to 2790.86 days for herd life, 925.71 to 1741.80 days for productive life, 8.94 kg for lifetime milk yield per day of lactating life and 3.93 to 7.32 kg for lifetime milk yield per day of productive life. Due to the significant and positive correlation amongst estimated breeding value of lifetime production traits selection based on these traits will be useful for improvement in the herd.
Keywords: Phule Triveni; sire; estimated breeding value; lifetime traits